Analisis Faktor-Faktor Keputusan Pembelian Makanan Dengan Menggunakan Jasa ShopeeFood - Putri Ayu Kusuma Wardani; Fadzlian Rizky Reinaldy; Indraswari Pramudaning Tyas (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
The technology advances can creat a market using e-commerce digital media, such as ShopeeFood. The use of ShopeeFood is motivated by purchasing decisions using ShopeeFood services by consumers. This study aim to examine the factors that influence purchasing decision using ShopeeFood services among students at UIN Raden Mas Said Surakarta. The research used a qualitative approach with interviews and observation as techniques for collecting the data. The informants of this research were UIN Raden Mas Said Students from various study programs who had used ShopeeFood service at least more than three times in ordering food. The researcher used the member checking method to check the validaty of the data. Based on the result of the study showed that the factors thaht influence the decision to buy used ShopeeFood service are the desire to save money with discounts or promos, efficient time, many ShopeeFood drivers, accessible location, and product completeness as dessired. The research can be evaluated for ShopeeFood in managing its business.